Thinking Outside the Frame: Impacting Genomes Capacity by Programmed Ribosomal Frameshifting - Riegger, Ricarda J.; Caliskan, Neva (Frontiers in Molecular Biosciences, 2022)
Translation is an integral part of cellular metabolism and therefore, is highly regulated. Here, RNA structures play an essential role in determining the rate and fidelity of translation. However, regulatory RNA structures exist also within the coding part, which program ribosomes to move to an alternative reading frame. In contrast to erroneous frameshifting, programmed ribosome frameshifting (PRF) is very efficient and produces functional polypeptides from an alternative reading frame. Recent technical advances in the translation field enabled the identification of precise mechanisms as to how and when ribosomes change the reading frame on mRNAs. Several studies indicate that tRNA abundance and trans-acting RNA modulators dynamically regulate the timing and efficiency of PRF. This highlights that frameshifting may fine-tune the proteome composition. Here, we intend to summarize these new findings and emphasize how it fits in our current understanding of PRF mechanisms as previously described.